Improving students’ reading comprehension by using listen, read, and discuss strategy at 5th semester English education department, IAIN Sultan Amai Gorontalo - Lamala, Dewi Astuti; Pakaja, Marina; Ismail, Abdul Kadir (Journal of English Teaching and Linguistic Issues (JETLI), 2023)
This research aim to improve students’ reading comprehension using Listen-Read-Discuss strategy. Two cycle of classroom action research were used in this research. Each cycle included two meetings. There were 15 students from 5th semester English Education Department, IAIN Sultan Amai Gorontalo that served as research participants. 20-question multiple choice tes and observation sheets of student and teacher activities were used as research instruments. Observation, tests, and documentation were enployed as data collection methods. The findings suggested that using Listen-Read-Discuss strategy coul enhance students’ reading comprehension. Before using Listen-Read-Discuss strategy, the average pre-tes score increased by 46.66 points, and after using Listen-Read-Discuss strategy, the average post-tes score increased by 71.33 points or 40% in cycle 1, and by 84.66 points or 87%, in cycle 2. It is suggested that English language teachers and learners can use Listen-Read-Discuss strategy in the classroom. For future research, it is recomended to obtain students’ vocabulary using Listen-Read-Discuss, namely through the text they read.